Exploring Servant Leadership and Work Commitment on Service Quality in Small and Medium Enterprises in the Agricultural Sector in Karawang, West Java - Asep Sutarman; Ahmad Kadim; Chua Toh Hua; Sondang Visiana Sihotang (International Journal of Engineering, Science and Information Technology, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the national economy. MSMEs are a populist economic system that can help alleviate poverty, and their growth has the potential to expand the economic base and contribute significantly to improving the regional economy and national resilience. The large number of MSMEs can become government partners in resource management. The MSME development strategy focuses on the agricultural sector in Karawang Regency. The success or failure of government policies in advancing MSMEs in the agricultural sector in Karawang Regency depends heavily on leadership, work commitment, and service quality. No company can develop or operate well until MSME participants provide exceptional service quality, work commitment, and service leadership. Therefore, it is important to address service problems in the MSME sector, especially in the agricultural sector in Karawang Regency. The main objective of this study is to empirically investigate the impact of servant leadership and work dedication on service quality. Data were collected using an online survey distributed to 259 SMEs in the agricultural industry in Karawang Regency, Indonesia. Data were evaluated using SEM. Hypotheses were assessed directly and jointly using two-step Partial Least Squares (PLS) path modelling. Based on the research findings, servant leadership had a higher influence value of 30.5% in influencing service quality than work commitment, which had a value of 22.4%. Mediation testing using the Sobel test resulted in a t-statistic value of 2.33 1.96 and a one-sided p-value of 0.00 0.05. Work dedication is an effective mediating component to increase the impact of servant leadership on service quality.